KINERJA PT. JASA RAHARJA (PERSERO) DI JAWA TENGAH (2012-2014) - Juli Franinta Siregar; Drs. Purwoko, M.S Drs. Purwoko, M.S; Dra. Sulistyowati, M.Si Dra. Sulistyowati, M.Si (Journal of Politic and Government Studies, 2015)
Traffic accidents are a global public health problem that is faced by all countries in the world, especially developing countries. This is certainly the high number of accidents caused by many factors, either because of human error (human error), technical errors, and nature. In Indonesia, the biggest cause of accidents caused by human error, which reached 90%. When you look at these facts, it should have the potential for a reduced number of accidents, due to human error factor is a factor that can be prevented by humans.The presence of PT JasaRaharja (Persero) as insurance Indonesian Society, provide protection to the public During the period of 54 years, PT JasaRaharja (Persero) is able to be a friend of the community. The main function of implementing and supporting the government's policy program in the field of national economic development, especially to improve the welfare of the people through the implementation of social insurance in accordance with JasaRaharjathe tagline